EKONOMI SIRKULAR DALAM INDUSTRI MANUFAKTUR: STRATEGI UNTUK MENGURANGI LIMBAH DAN MENINGKATKAN EFISIENSI - Sari, Urmila; Rusdiantini, Sansy; Novianti, Sri; Maulidiah, M (Jurnal Ekonomi & Bisnis, 2025)
Continuous population growth and consumption have pushed the manufacturing industry to face significant challenges related to resource and waste management. The linear economic model of "take-use-dispose" is no longer sustainable. The circular economy offers a promising alternative approach, focusing on extending product life, reducing waste, and recovering value. The shift to a circular economy in manufacturing industries has been deemed as a frontrunner among strategies to deal with resource efficiency and sustainable development concerns. This article analyzes various strategies for implementing a circular economy in the manufacturing sector, including design for circularity, industrial symbiosis, recycling and reuse practices, and service-oriented business models. The primary objective is to examine how these strategies can substantially reduce waste, increase resource efficiency, and ultimately create competitive advantage for corporations. This study used a qualitative method with a literature review approach. In the context of this research, the literature study method is used as a descriptive basis for compiling an analytical narrative regarding the application of a circular economy in the manufacturing industry as an effort to reduce waste and increase efficiency. The results of this study show that the prospect of CE goes far beyond environmental protection as it helps to build economic stability, create new working places, and gain competitive advantages in the global economy. Nevertheless, some key barriers remain; poor standardization, technological limitations and cultural issues. It is only possible to fix these problems via innovations for these issues, the multi-stakeholder cooperation, and the sound policies for creating a sustainable industrial revolution.